2017
DOI: 10.1186/s12879-017-2252-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Vibrio cholerae O1 isolates from outbreaks between 2011 and 2015 in Tanzania

Abstract: BackgroundCholera outbreaks have occurred in Tanzania since 1974. To date, the genetic epidemiology of these outbreaks has not been assessed.Methods96 Vibrio cholerae O1 isolates from five regions were characterized, and their genetic relatedness assessed using multi-locus variable-number tandem-repeat analysis (MLVA) and whole genome sequencing (WGS).ResultsOf the 48 MLVA genotypes observed, 3 were genetically unrelated to any others, while the remaining 45 genotypes separated into three MLVA clonal complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
3
30
0
1
Order By: Relevance
“…The V. cholerae O1 global phylogeny including data from Uganda [15], Tanzania [49], DRC, Central African Republic, and Zambia [5] confirms that the ST515 sub-clade has now spread to several regions of Central and Eastern Africa, including western provinces of DRC up to the Atlantic coast. Whereas the reason why only the ST515 expands so widely, and not the ST69 sub-clade, remains unknown, the hypothesis is that the higher genetic diversity among ST515 isolates results from a high mutation frequency, which favors their adaptation to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 92%
“…The V. cholerae O1 global phylogeny including data from Uganda [15], Tanzania [49], DRC, Central African Republic, and Zambia [5] confirms that the ST515 sub-clade has now spread to several regions of Central and Eastern Africa, including western provinces of DRC up to the Atlantic coast. Whereas the reason why only the ST515 expands so widely, and not the ST69 sub-clade, remains unknown, the hypothesis is that the higher genetic diversity among ST515 isolates results from a high mutation frequency, which favors their adaptation to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Genomic DNA was extracted from 38 isolates using published phenol-chloroform extraction methods [ 23 ]. Genome sequencing was performed as previously published on an Illumina HiSeq2500 (Illumina, San Diego, CA, USA) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…We choose the wave 3 isolate genome, S002604, as the reference, in order to minimize the number of variable sites that were different between the reference genome and all the genomes in our sample since those variable sites do not contribute to the analysis. PARSNP (v1.2) [ 28 ] was used to extract and align the variable nucleotides using previously published options [ 24 , 25 ]. The ‘.ggr’ file was loaded in Gingr (v1.2) [ 28 ] to visualize the alignments.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas random sampling is ideal, it is difficult to implement during epidemics because of competing priorities. Furthermore, although studies have shown that 6-locus MLVA can be highly discriminative for identifying a closely related pandemic strain isolated in a small timeframe and geographic area ( 12 , 13 ), our lack of knowledge of MLVA limitations makes it more difficult to draw inferences about strain relatedness and phylogenetic history, especially compared with whole-genome sequencing ( 14 ). …”
Section: The Studymentioning
confidence: 99%